KEPEMIMPINAN TRANSFORMASIONAL DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR DALAM MENINGKATKAN KINERJA GURU - Sri Suratiyah (Wahana Islamika: Jurnal Studi Keislaman, 2018)
Efforts to provide educational stimuli and develop every potential of children, requires the existence of teacher roles and performance that is to support the success of early childhood in developing creativity and all the potential that exists in children. Teachers are the most influential component to the creation of quality education processes and results. Based on this, this study aims to examine the effect of teachers' perceptions on transformational leadership and Organizational Citizenship Behavior (OCB) on teacher performance. This study uses quantitative approach with the number of research subjects which amounted to 79 consisting of PAUD teachers in District Sedayu. The method of analysis used this research is multiple linier regression analysis. The results found that the perception of transformational leadership and organizational citizenship behavior had a positive and significant influence on teacher performance. In addition, the study also found that transformational leadership perceptions have greater influence on teacher performance when compared to the effects of organizational citizenship behavior on teacher performance.